LIP PRINT PATTERN ON DIFFERENT MEDIAS: A FORENSIC IDENTIFICATION TOOL (Journal of Forensic Medicine & Toxicology, 2021)
Role of lip prints in identification is very vast. Study of lip prints is known as cheiloscopy1.lip prints are wrinkles or grooves present in the transition zone of human lip between inner labial mucosa and outer skin. These wrinkles or grooves present on the lips have been named by Tsuchihashi as “sulci labiorum rubrorum”2. Identification through lip prints is same as finger print. As finger prints are used for absolute identification, similarly lip prints are used for the same. But nowadays identification through lip prints is gaining attention as criminals are taking precautions like the use of gloves or silicon thumbs, so that their finger prints may not be identified. Like finger prints, lip prints are also unique to the individual. The location of lip print at the scene of crime gives much valuable information about the individual and his habits e.g. lip prints on drinking glass or on a cigarette. Since 1950, Japanese have carried out extensive research in the matter of cheiloscopy. Tsuchihashi in japan studied lip print impressions called “KO SHIMON”(mouth fingerprints) in Japanese. Based on research done by Suzuki and Tsuchihashi3, it was established that the arrangement of lines on red part of human lips is individual and unique for each human being. The lip prints being uniform throughout life and characteristics of person can be used to verify the presence or absence of a person from the crime4 provided there has been consumption of beverages, drinks, usage of cloth, tissue or napkin etc at the crime scene. By comparing the composition of a lipstick smear with that of a victim or a witness, Forensic Scientist can demonstrate direct or indirect proof of contact or a relationship between plaintiff
Keywords: Lip prints; Identification